Achieving fast and durable alkali-ion storage by designing gradient interface with low charge transfer barrier. (July 2021) - Que, Lan-Fang; Yu, Fu-Da; Xia, Yang; Deng, Liang; Jiang, Yun-Shan; Han, Yi; Wang, Zhen-Bo
Abstract: Compared with Li-ions, it is difficult to achieve fast dynamics for Na/K-ion storage. H-titanates as potential candidates suffer from low theoretical capacity, limiting the energy density of full cells. Herein, we report an Sn(Ⅱ)/Sn(Ⅳ) gradient doping strategy to simultaneously realizes the construction of a disordered interface with abundant defects and well-organized interlayered structure with larger interlayer spacing in H-titanate. The interfacial-located Sn 2+ with a larger ionic radius triggers surface structural distortion to realize a favorable electronic structure with a narrower bandgap. Meanwhile, the interlayer-located Sn 4+ plays a pillar effect to enhance the structural stability and modify the interlayer ion transport channel. Based on the analysis of ex-situ XRD, time of flight secondary ion mass spectrometry and temperature-dependent EIS, it is found that Sn(Ⅱ)/Sn(Ⅳ) gradient doping can effectively enhance structural stability, lower charge transfers barrier and boost ion diffusion kinetics, then resulting in 2.4- and 1.5-fold improvement for Li-ion and Na-ion storage, high capacity of 223 mAh g −1 and long cycle stability over 1800 cycles for K-ion storage. When used as additive-free anodes for hybrid capacitors, impressive energy densities in Li/Na-ion systems and superior cycle stability in Na/K-ion configurations have been achieved. These findings indicating that Sn(Ⅱ)/Sn(Ⅳ) gradient doping strategy has significant advantages for fast and durable alkali-ion storage. Graphical Abstract: A Sn(Ⅱ)/Sn(Ⅳ) gradient doping strategy is proposed to promote Li/Na/K-ion storage performance by facilitating ion diffusion kinetics and lowering charge transfer barrier, which is conducive to deeply understand the complex ion storage dynamics and charge transfer kinetics and provide new ideas for designing advanced energy storage materials. ga1 Highlights: A Sn(Ⅱ)/Sn(Ⅳ) gradient doping is proposed to construct disordered interface and expand interlayer structure of HTO. Sn(Ⅱ)/Sn(Ⅳ) gradient doping can effectively lower charge transfers barrier and boost ion diffusion kinetics. 2.4- and 1.5-fold improvement in LIBs and SIBs, capacity of 223 mAh g -1 and long cycle stability in KIBs are achieved. When used as additive-free anodes for hybrid capacitors, high energy densities and long cycle stability are obtained.